A Fuzzy Logic Technique for Optimizing Follicular Units Measurement of Hair Transplantation - Mostafa S.A.; Alsobiae A.S.; Ramli A.A.; Mustapha A.; Ali R.R. (Springer, 2023)
Computer circuits; Data mining; Extraction; Soft computing; Area density; Fuzzy logic system; Fuzzy logic techniques; Fuzzy metrics; Human skin; Medical procedures; Fuzzy logic